Pengaruh Gaya Kepemimpinan, Kepuasan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Dinas Perdagangan Kota Surakarta - Aji Fajar Pangestu; Asih Handayani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The research is aimed at studying the significance of the influence of leadership style, job satisfaction, and work motivation on the performance of the Dinas Perdagangan Kota Surakarta. This form of research is a survey. The population in this study is 203 employees of the Dinas Perdagangan Kota Surakarta. Samples in this research of 67 employees of the Dinas Perdagangan Kota Surakarta were obtained from the Slovin formula. Sampling method using random sampling techniques. The research uses a method of descriptive data analysis, as well as a double linear regression analysis. Data collection strategy using a questionnaire. The findings show that leadership styles, job satisfaction and motivation have a significant impact on the performance of Dinas Perdagangan Kota Surakarta